What is the Identity of Interdisciplinarity? - Lange, Michael (Journal of Interdisciplinary Studies in Education, 2019)
Interdisciplinarity is nothing new. The earliest attempts to understand,organize, or codify knowledge and learning were infused with what todaylook like interdisciplinary thinking and approaches. Indeed, interdisciplinarityonly makes sense if it is preceded by some system of disciplines that perceivethemselves and/or are perceived to be separable and bounded. There have tobe lines to transcend, categories to move between, before something can be“inter-” anything. So to call the education of philosopher kings in Republicinterdisciplinary is a bit anachronistic, as the current forms ofinterdisciplinarity are rooted in the post-Enlightenment and modern divisionswithin academia, well post-dating Plato. It was in that post-Enlightenmentmoment when disciplinary beliefs and practices made the biggest leap towardbecoming disciplinary identities as well.